How Do Organizational Culture and Innovation Trigger Successful Management of Public Institutions? - Irina TARABAN; Maria Andreea TILIBASA; Alina Nicoleta DOBRE; Dorin Felician MARCHIS; Lucica TUDORAN (Communications of International Proceedings, 2022)
Nowadays, successful management is an essential condition for any organization, especially in public institutions that are not based on the principle of profit and loss. The need for efficient management in the public sector is the result of technological changes that involve reinventing management paradigms through relevant processes, tools and instruments that will help us cope with a complex, dynamic and interconnected society. In such a digitalized environment, organizational culture will take a different shape when compared to traditional culture suggesting that organizations in favor of digital culture embrace innovation, encourage collaborative work, and support risk-taking actions. Through such a culture, organizations could gain a competitive advantage making good use of digitalization. This article aims to highlight how organizational culture and innovation can lead to successful management in the public sector based on the results obtained through a descriptive analysis of the existing literature. The review builds on academic articles from major databases as well as on published sources. The results provide evidence that organizational culture and innovation are central pieces for successful management in the public sector. The literature review represents just a reference frame meant to further stimulate research on the role of organizational culture and innovation in the public sector’s successful management.
Keywords: innovation; management; organizational culture; public institutions